Measuring of Mycobacterium tuberculosis growth: a correlation of the optical measurements with colony forming units - Peñuelas Urquides, Katia; Villarreal Treviño, Licet; Silva Ramírez, Beatriz; Rivadeneyra Espinoza, Liliana; Said Fernández, Salvador; León, Mario Bermúdez de (2013)
The quantification of colony forming units (cfu), turbidity, and optical density at 600 nm (OD600) measurements were used to evaluate Mycobacterium tuberculosis growth. Turbidity and OD600 measurements displayed similar growth curves, while cfu quantification showed a continuous growth curve. We determined the cfu equivalents to McFarland and OD600 units